Pertanggungjawaban Pidana Korporasi Dalam Tindak Pidana Pencucian Uang Menurut Undang-Undang Nomor 8 Tahun 2010 Tentang Pencegahan Dan Pemberantasan Tindak Pidana Pencucian Uang - Habibi, Muhammad; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Money laundering is a criminal offense which can cause a broad impact, especially in the field of economy. In addition to individuals, money laundering can also be done by the corporation. The purpose of this paper is first, to determine the forms of money laundering by corporations, secondly, to determine corporate criminal responsibility in the crime of money laundering in accordance with Law No. 8 of 2010 on the Prevention and Combating of Money Laundering.Writing this research uses normative law research that examines the legislation and the principles of law, namely Law No. 8 of 2010 on the Prevention and Combating Money Laundering and few regulations that exist in Indonesia, which refers to the Code OF THE Criminal Law. This research has a descriptive nature, which is a form of research that aims to create a picture of the problem. Source of data used is data sekunderyang consists of primary legal materials, secondary and tertiary. Datametode collection techniques literature studies or study documents such as books, magazines, journals and the legislation in force. Thus, this study has the relationship between the data contained either in the legislation or in the literature.From the research problem, there are two main things that can be inferred. First, the forms of money laundering by corporations is divided into three types, namely placement, pelapisandanpenggabungan. Second, the corporation can be sentenced to a basic form of criminal fines and additional penalty. If the penalty is not able to pay, then it can be replaced with the seizure of the property of the corporation and the corporation controlling personnel, and if insufficient, then the substitute imprisonment imposed fines against corporate control personnel. The first author's suggestion, the performance of the law enforcement field should be done carefully and thoroughly so as to avoid loopholes for perpetrators to escape unpunished. Second, to succeed the money laundering law enforcement, law enforcement officers in each line must process the corporation if the corporation is involved in money laundering.Keywords: Accountability Pidana- corporations-Laundering